2013
DOI: 10.1016/j.mehy.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The p53–microRNA-34a axis regulates cellular entry receptors for tumor-associated human herpes viruses

Abstract: A growing number of reports indicate the frequent presence of DNA sequences and gene products of human cytomegalovirus in various tumors as compared to adjacent normal tissues, the brain tumors being studied most intensely. The mechanisms underlying the tropism of human cytomegalovirus to the tumor cells or to the cells of tumor origin, as well as the role of the host’s genetic background in virus-associated oncogenesis are not well understood. It is also not clear why cytomegalovirus can be detected in many b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 92 publications
0
4
0
1
Order By: Relevance
“…[ 25 ] In addition, it has been demonstrated that ectopic miR-34a could induce apoptosis when reintroduced into some cancer cells because it represses SIRT1, YY1, and Bcl-2, in which, miR-34a was identified as a p53 target, and miR-34a mediated apoptosis may be suppressed by the inactivation of p53. [ 15 26 27 ] MiR-34a was down-regulated in many cancers, including gastric cancer. [ 28 ] Bhatt et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] In addition, it has been demonstrated that ectopic miR-34a could induce apoptosis when reintroduced into some cancer cells because it represses SIRT1, YY1, and Bcl-2, in which, miR-34a was identified as a p53 target, and miR-34a mediated apoptosis may be suppressed by the inactivation of p53. [ 15 26 27 ] MiR-34a was down-regulated in many cancers, including gastric cancer. [ 28 ] Bhatt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because p53 is known to increase transcription of many microRNAs (miRNAs), we wondered whether some miRNAs could be involved in CD46 decrease, as miR31 and miR128 were shown to regulate PVRL4 expression and MV infection in nohematopoietic cells. [37][38][39] We treated 2 TP53 wt HMCLs with nutlin3a for 15 hours and analyzed miRNA expression using an miRNA PCR array (supplemental Table 3). Expression of 11 and 9 miRNAs with a significant score against CD46 was increased more than 1.4-fold in MM1S and BCN, respectively, and 3 were shared between the 2 HMCLs (miR34a#, miR192#, and miR571) (Figure 4B).…”
Section: P53 Directly and Indirectly Regulates Cd46 Expressionmentioning
confidence: 99%
“…Each human tissue is characterized by a specific set of miRNAs which may constitute an innate characteristic of that tissue [11, 41]. Moreover, an increasing number of experimental researches have demonstrated that some miRNAs have the potential to modulate the in vivo tissue tropism of multiple viruses [4244]. So it can be plausible that there is substantial heterogeneity in miRNA expression profile if different tissue cell models were used for the infection of certain pathogen, which depends on further investigation in the near future.…”
Section: Discussionmentioning
confidence: 99%